Monitoring rocky shores - Murray, Steven N. (Steven Nelson), 1944- (University of California Press, 2006)
Monitoring changes in the intertidal zone of rocky shores has never been more critical. This sensitive habitat at the interface of land and ocean may well be the marine equivalent of the canary in a coal mine as we advance into an era of global climate change. This handbook describes effective methods and procedures for monitoring the ecological and environmental status of these areas. Written by three collaborating authors with extensive field experience, it provides critical discussions and evaluation of the various sampling techniques and field procedures for studies of intertidal macroinvertebrates, seaweeds, and seagrasses. Rather than prescribing standard protocols or procedures, the authors break down the decision-making process into various elements so investigators can become aware of the advantages and disadvantages of choosing a particular method or approach. Chapters discuss topics such as site selection, field sampling layouts and designs, selection of sampling units, nondestructive and destructive methods of quantifying abundance, and methods for measuring age, growth rates, size, structure, and reproductive condition.